An outbreak of meningococcal disease in Stonehouse: planning and execution of a large-scale survey. - Stuart, J. M. (Cambridge University Press, 1987)
In November 1986 a large-scale survey was undertaken in the Gloucestershire town of Stonehouse during an outbreak of meningococcal disease due to group B type 15 subtype P1.16 sulphonamide-resistant strains. There were 15 cases in Stonehouse residents during the 4 years from April 1983, an annual attack rate of 56.5 per 100,000. Four secondary cases occurred despite rifampicin prophylaxis. The objectives of this community survey were to investigate patterns of meningococcal carriage, transmission and immunity and to determine the proportion of non-secretors of blood group antigens in the Stonehouse population and amongst meningococcal carriers. A total of 6237 subjects participated including 75% of the 6635 Stonehouse residents. Over 97% of the participants provided all three of the requested specimens-nasopharyngeal swabs, saliva and blood samples. The co-operation between the many organizations involved in the detailed preliminary planning was instrumental in the success of the survey; in particular the value of effective collaboration between Departments of Community Medicine and Microbiology and of the Public Health Laboratory Service network of laboratories in undertaking investigations of this size and type was clearly demonstrated.